Plastic Solid Waste (PSW) in the Context of Life Cycle Assessment (LCA) and Sustainable Management - Antelava, Ana; Damilos, Spyridon; Hafeez, Sanaa; Manos, George; Al-Salem, Sultan M.; Sharma, Brajendra K.; Kohli, Kirtika; Constantinou, Achilleas (My University, 2019)
Over the past few decades, life cycle assessment (LCA) has been established as a critical tool for the evaluation of the environmental burdens of chemical processes and materials cycles. The increasing amount of plastic solid waste (PSW) in landfills has raised serious concern worldwide for the most effective treatment. Thermochemical post-treatment processes, such as pyrolysis, seem to be the most appropriate method to treat this type of waste in an effective manner. This is because such processes lead to the production of useful chemicals, or hydrocarbon oil of high calorific value (i.e. bio-oil in the case of pyrolysis). LCA appears to be the most appropriate tool for the process design from an environmental context. However, addressed limitations including initial assumptions, functional unit and system boundaries, as well as lack of regional database and exclusion of socio-economic aspects, may hinder the final decision. This review aims to address the benefits of pyrolysis as a method for PSW treatment and raise the limitations and gaps of conducted research via an environmental standpoint.
Keywords: Pyrolysis; Plastics; Sustainable Management; Recycling; Energy; LCA